2010
DOI: 10.1097/id.0b013e3181effa92
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular Nerve Neurosensory Impairment After Dental Implant Surgery: Management and Protocol

Abstract: More than 70% of dentists have experienced patients with postoperative paresthesia/dysesthesia or anesthesia as a result of dental procedures. The most common nerve affected is the mandibular nerve, which may be injured during either implant surgery or bone grafting procedures. However, no organized protocol directed specifically for general dentists, or for the vast majority of specialists, has been published. The protocol presented in this article is divided into 5 periods: during surgery (1) nerve injury is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
69
0
14

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(83 citation statements)
references
References 23 publications
0
69
0
14
Order By: Relevance
“…A detailed consultation with a full explanation of their symptoms and nerve injury seemed to alleviate many concerns and anxieties, as seen by the 13 patients in this study who were discharged after 2-4 consultations. Early referral to a nerve specialist, as also suggested by Misch and Randolph, 37 is therefore helpful for the management of patients with nerve injury. Honesty in estimating the likeliness of their injury improving also provides the patients with realistic goals.…”
Section: Postoperativelymentioning
confidence: 99%
“…A detailed consultation with a full explanation of their symptoms and nerve injury seemed to alleviate many concerns and anxieties, as seen by the 13 patients in this study who were discharged after 2-4 consultations. Early referral to a nerve specialist, as also suggested by Misch and Randolph, 37 is therefore helpful for the management of patients with nerve injury. Honesty in estimating the likeliness of their injury improving also provides the patients with realistic goals.…”
Section: Postoperativelymentioning
confidence: 99%
“…The incidence of dental implant related nerve sensory damage (NSD) has been shown to be as high as 40% in past studies [8,11,[13][14][15][16][17][18][19][20] although at least one prospective large cohort study has shown that risk of TG injuries can be eliminated with meticulous attention to planning and observing good surgical protocols. [61] Nevertheless, the large variation in the reported incidence of NSD suggests that this serious complication of dental implant surgery has not yet been adequately evaluated and reported.…”
Section: Incidence Of Tg Injuriesmentioning
confidence: 99%
“…[1][2][3] TG injuries are characterized by neurosensory disturbances, such as pain, numbness or altered tingling-type sensations (paraesthesia), within the teeth, skin and the mucosa. [4][5][6][7] The inferior alveolar nerve (IAN) and mental nerve (MN) and the lingual nerve (LN) are the most commonly damaged nerves during dental implant treatment [6,[8][9][10][11][12] with some studies reporting an incidence rate of up to 40% of nerve damage following implant placement surgery in the mandible related to the depth and the width of the implant bed preparation. [8,11,[13][14][15][16][17][18][19][20] Local anesthetic injections also cause TG damage due to mechanical or chemical injury.…”
mentioning
confidence: 99%
See 2 more Smart Citations